Effect of Vitamin D3 Supplement on the Semen Quality in Human Patients with Vitamin D Deficiency - Hayder H. Abed; Aamer M. Ali; Zahrah S. Mahdi (Bogor Agricultural University, Indonesia, 2022)
Male fertility is a complicated process that can be hampered by a variety of lifestyle factors. This study aims to evaluate the effect of vitamin D3 deficiency on the semen quality and also to study the quality changes in the semen of patients with vitamin D3 deficiency, after supplementation with vitamin D3 for a month. This present study included 112 participants, who were classified into two groups according to the serum level of vitamin D3 (normal and deficiency groups). The semen was analyzed by the physical examination of both groups; also this study included follow-up patients with vitamin D3 deficiency, who were supplied with 5,000 IU of vitamin D3. The results showed a significant decrease in the motility of sperms in patients with vitamin D3 deficiency (27.16%±2.497%) compared to the standard group (36.71%±2.892%), and an increase in sperm motility in patients who consumed vitamin D3, after being followed up for a month (37.19%±2.836%). Moreover, the result showed a high and significant increase in the rate of deformities of sperms in patients with vitamin D3 deficiency (18.67%±1.074%) compared to the standard group (13.68%±0.8131%) and a decrease in the rate of deformities of sperms in patients who took vitamin D3 supplement for a month (13.54%±0.8116%). The study concluded that patients with a supplement intake of vitamin D3 had an effect on the semen quality, especially the motility and deformity of sperms in vitamin D3-insufficient men.